2002
DOI: 10.1001/archinte.162.12.1349
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil for Male Erectile Dysfunction

Abstract: Sildenafil improves erectile function and is generally well tolerated. Treatment response seems to vary between patient subgroups, although sildenafil has greater efficacy than placebo in all evaluated subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(23 citation statements)
references
References 31 publications
(36 reference statements)
0
23
0
Order By: Relevance
“…Despite clinical trials data illustrating a high level of efficacy (successful sexual intercourse attempt rates for sildenafil were 83% vs 45% with a placebo [4]) and a discontinuation rate as low as 7% [4], PDE5i usage suffers a significant dropout rate of about 50% [5]. This observation is not explained by the natural course of the disease.…”
Section: Introductionmentioning
confidence: 94%
“…Despite clinical trials data illustrating a high level of efficacy (successful sexual intercourse attempt rates for sildenafil were 83% vs 45% with a placebo [4]) and a discontinuation rate as low as 7% [4], PDE5i usage suffers a significant dropout rate of about 50% [5]. This observation is not explained by the natural course of the disease.…”
Section: Introductionmentioning
confidence: 94%
“…6,7 Reasons for this include a lack of training of health care professionals, discomfort of providers with the topic, and insufficient time during visits for discussion. 1 However, effective strategies for treating both female and male sexual dysfunction exist, 811 making these discussions a critical part of survivorship care.…”
Section: Overviewmentioning
confidence: 99%
“…8,10 Many studies have also shown the efficacy and tolerability of PDE5i for treating ED in patients with cancer and survivors. 24,25 Importantly, PDE5is are contraindicated in patients taking oral nitrates, because together they can lead to a dangerous decrease in blood pressure.…”
Section: Interventions For Male Sexual Dysfunctionmentioning
confidence: 99%
“…This approach yielded several classic drugs. One is sildenafil, which was originally discovered as a treatment for various cardiovascular disorders in 1989 and now is sold with the brand name Viagra to treat erectile dysfunction (Fink et al, 2002). Another is azidothymidine, which originally failed as a chemotherapy anticancer drug due to the lack of efficacy but emerged in the 1980s as a therapy for HIV (D'Andrea et al, 2008).…”
Section: Introductionmentioning
confidence: 99%